New fluorinated agonists for targeting the sphingosin-1-phosphate receptor 1 (S1P1). Issue 22 (15th November 2015) - Shaikh, Rizwan S.; Keul, Petra; Schäfers, Michael; Levkau, Bodo; Haufe, Günter
Graphical abstract: Abstract: The sphingosine-1-phosphate receptor type 1 (S1P1 ) is involved in fundamental biological processes such as regulation of immune cell trafficking, vascular barrier function and angiogenesis. This Letter presents multistep syntheses of various fluorine substituted 12-aryl analogues of the drug fingolimod (FTY720) and a seven-steps route to 2-amino-17, 17-difluoro-2-(hydroxymethyl)heptadecan-1-ol. In vitro and in vivo tests proved all these compounds as potent S1P1 receptor agonists.